ANALYSIS OF FIGURATIVE LANGUAGE IN THE NOVEL THE KITE RUNNER - Rini Amir; Samsudin Hi. Adam; Agus Supriyadi (Universitas Khairun, 2024)
The purpose of this research is to find out and analyze the types of figurative language and its meaning in the novel